AN ANALYSIS ON LANGUAGE FUNCTION OF “THE MIRACLEWORKER” MOVIE SCRIPT - Aan Selviatul Qomariah (The Ellite of Unira, 2019)
The Miracle Worker” movie is a good movie that appropriate to be inspected. This movie has wonderful story because the film was nominated for five Academy awards, including best Director for Arthur Penn. “The miracle Worker” also holds a perfect 100% score from the movie critics site Rotten Tomatoes. Data source in this research will be got from two source that from documentation and movie script in “The Miracle Worker”. The researcher will get some information or data based on watching the movie, made and match the script, and identified the script. The purpose of this research are with the Function of language (directive function) can help the reader on analyses of the film. In the “Miracle Worker” movie The researcher found directive function, in the directive function the researcher divided into two section, are : instruction and restriction. So, the reader can know the means about directive function on function of language